Enhanced piezoresponse of electrospun PVDF mats with a touch of nickel chloride hexahydrate salt - Dhakras, Dipti; Borkar, Vivek; Ogale, Satishchandra; Jog, Jyoti Prakash (Nanoscale, 2012)
PVDF nanofibers are prepared using electrospinning. The effect of addition of a hydrated salt, nickel chloride hexahydrate (NiCl2 center dot 6H(2)O), on the phase formation is examined. Addition of the hydrated salt (NC) is found to enhance the polar beta phase by about 30%. The peak to peak piezo-voltage generated for PVDF NC is almost 0.762 V, a factor of 3 higher than that for PVDF. The fiber mats exhibit a significantly enhanced dynamic strain sensor response. The voltage generated per unit micro-strain developed during the free vibration test for PVDF was 0.119 mV whereas it was 0.548 mV for PVDF NC, exhibiting a non-linearly enhanced performance vis a vis the increase in the beta phase component.

Fluorinated nanocellulose-reinforced all-organic flexible ferroelectric nanocomposites for energy generation - Ram, Farsa; Ambone, Tushar; Sharma, Aakash; Murugesan, Rajarathinam; Kajale, Deepak; Borkar, Vivek; Ali, Shaikh Faruque; Balu, Praveen Kumar; Kumaraswamy, Guruswamy; Shanmuganathan, Kadhiravan (Journal of Physical Chemistry C, 2018)
We report here enhanced ferroelectric crystal formation and energy generation properties of polyvinylidene fluoride (PVDF) in the presence of surface-modified crystalline nanocellulose. Incorporation of only 2-5 wt % fluorinated nanocellulose (FNC) in PVDF has been found to significantly induce polar beta/gamma-phase crystallization as compared to the addition of unmodified nanocellulose (carboxylated nanocellulose). A device made up of electrically poled PVDF/FNC composite films yielded 2 orders of magnitude higher voltage output than neat PVDF in vibrational energy harvesting. This remarkable increase in energy generation properties of PVDF at such a low loading of an organic natural biopolymer could be attributed to the tailored surface chemistry of nanocellulose, facilitating strong interfacial interactions between PVDF and FNC. Interestingly, energy harvesting devices fabricated from PVDF/FNC nanocomposites charged a 4.7 mu F capacitor at significantly faster rate and the accumulated voltage on capacitor was 3.8 times greater than neat PVDF. The fact that PVDF/FNC nanocomposites still retain a strain at break of 10-15% and can charge a capacitor in few seconds suggests potential use of these nanocomposites as flexible energy harvesting materials at large strain conditions.

Nanocellulose reinforced flexible composite nanogenerators with enhanced vibrational energy harvesting and sensing properties - Ram, Farsa; Gudadhe, Aniket; Vijayakanth, Thangavel; Aherrao, Swapnil; Borkar, Vivek; Boomishankar, Ramamoorthy; Shanmuganathan, Kadhiravan (2020)
We report here enhanced vibration and pressure sensing properties of nanocellulose reinforced flexible composite piezoelectric nanogenerators (PENGs). Surface fluorinated nanocellulose crystals (FNC) were incorporated into poly(vinylidene fluoride) (PVDF) and electrospun into composite nanofibers. Incorporation of only 2 wt % FNC in PVDF resulted in a significant enhancement in pressure sensitivity with a very low detectable pressure limit of 10 Pa and a sensitivity of up to 18 mV/kPa. The composite PENGs also demonstrated very high sensitivity for forced continuous vibrations. 2FNC/PVDF composites resulted in an order of magnitude higher voltage response over neat PVDF for a given strain. When PENGs were mounted on a vacuum pump for transduction of mechanical vibrations into electrical energy, 2FNC/PVDF composite devices manifested similar to 3.8 times enhanced voltage output over neat PVDF and faster charging of a capacitor. The enhanced piezoelectric properties of PVDF/FNC nanocomposites could be attributed to the tailored interface between PVDF and nanocellulose and enhanced polarizability.
Keywords: Composite; Nanofiber; piezoelectric; pressure; Sensor; vibration